1999
DOI: 10.1016/s0009-9236(99)80120-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of SB-240563, a humanized monoclonal antibody directed to human interleukin-5, in mild asthmatics

Abstract: Clinical Pharmacology & Therapeutics (1999) 65, 147–147; doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 0 publications
1
43
0
Order By: Relevance
“…The Ab-02 PK parameters estimated by PK-PD modeling were consistent with those estimated by non-compartmental analysis (20). Ab-02 had a low clearance and a small volume of distribution in monkeys, typical of those seen for other humanized IgG1 therapeutic proteins (29)(30)(31). The PK-PD modeling further confirmed that Ab-02 volume of distribution was smaller in Ascaris-challenged monkeys when compared a For estimation of mean parameters in naive animals, three animals in the 1 mg/kg, IV group and two animals in the 2 mg/kg, SC group were used.…”
Section: Discussionsupporting
confidence: 58%
“…The Ab-02 PK parameters estimated by PK-PD modeling were consistent with those estimated by non-compartmental analysis (20). Ab-02 had a low clearance and a small volume of distribution in monkeys, typical of those seen for other humanized IgG1 therapeutic proteins (29)(30)(31). The PK-PD modeling further confirmed that Ab-02 volume of distribution was smaller in Ascaris-challenged monkeys when compared a For estimation of mean parameters in naive animals, three animals in the 1 mg/kg, IV group and two animals in the 2 mg/kg, SC group were used.…”
Section: Discussionsupporting
confidence: 58%
“…Indeed, a smaller clinical trial with another humanized anti-IL-5 antibody (reslizumab) has suggested that rebound eosinophilia might be related to subsequent overproduction of IL-5. 19,34 Mepolizumab has a half-life of 13 ± 2 days after intravenous administration, 35 but its biologic activity can be longer, as observed by the significant decrease in peripheral blood eosinophil levels that persisted for 3 months in 76% of subjects after the final mepolizumab infusion. Interestingly, in 33% of subjects, a partial to complete recovery of peripheral blood eosinophil levels (an increase of 50% or greater) was observed at week 28, approaching levels observed at week 8; an even greater effect on eosinophil levels was observed when corticosteroid therapy was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of pascolizumab in monkey plasma was determined using a selective electrogenerated chemiluminescence immunoassay similar to that described previously [16]. The lower limit of detection for pascolizumab was 50 ng/ml.…”
Section: Single-and Repeat-dose Toxicity Studies In Cynomolgus Monkeysmentioning
confidence: 99%